2020
DOI: 10.3892/mmr.2020.11157
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol alleviates diabetic mechanical allodynia in rats by downregulating P2X3R

Abstract: Mechanical allodynia, which develops in patients of diabetes mellitus as a neuropathic manifestation, remains without an effective treatment. The aim of the present study was to investigate the effects and potential mechanisms underlying resveratrol (reS) in a rat model of streptozocin (STZ)-induced diabetic mechanical allodynia (dMa). The rat model of dMa was established by the administration of an intraperitoneal injection of STZ. From day 8 post-STZ injection, rats were administered with an intragastric inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In addition, thermal hyperalgesia and mechanical allodynia are known as the most common forms of DNP. In 2020, Cui et al investigated the effects of RSV on diabetic mechanical allodynia (DMA)-related behaviors in rats ( 133 ). The results confirmed that the RSV had a dose-dependent analgesic effect on DMA model rats.…”
Section: Resveratrol Effects On Diabetic Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, thermal hyperalgesia and mechanical allodynia are known as the most common forms of DNP. In 2020, Cui et al investigated the effects of RSV on diabetic mechanical allodynia (DMA)-related behaviors in rats ( 133 ). The results confirmed that the RSV had a dose-dependent analgesic effect on DMA model rats.…”
Section: Resveratrol Effects On Diabetic Complicationsmentioning
confidence: 99%
“…The results confirmed that the RSV had a dose-dependent analgesic effect on DMA model rats. In addition, downregulation of P2X3R expression in the dorsal root ganglion (DRG) and spinal dorsal horn (SDH) might be the potential mechanism of RSV analgesic effects on DMA-related behaviors ( 133 ).…”
Section: Resveratrol Effects On Diabetic Complicationsmentioning
confidence: 99%
“…In Polygonum cuspidatum, resveratrol (RES) relieves pain in peripheral and central inflammatory diseases by decreasing arachidonic acid metabolism [80]. In addition, RES suppressed neuropathic pain transmission in DRG satellite glial cells and relieved mechanical hyperalgesia in rats treated with gp120 by inhibiting P2X3R and P2X7R [81][82][83][84]. Astragalin therapy has been reported to be able to reduce neuropathic pain by blocking P2X4-mediated signaling in rat DRG [85].…”
Section: Active Ingredients Of Tcms For Painful Diseases Management Via P2x3r and P2x7rmentioning
confidence: 99%